Antitumor activity of novel purine acyclic nucleotide analogs PMEA and PMEDAP - Otová, B; Zídek, Z; Holý, A; Votruba, I; Sladká, M; Marinov, I; Lesková, V (In vivo (Athens, Greece), 1997)
PMEDAP and/or PMEA treatment of SD rat lymphomas significantly prolonged the mean survival time of tumor-bearing animals. Dose-dependent genotoxicity of both PMEDAP and PMEA was not observed in in vitro tests on stabilized diploid MRC-5 cell line. The mitotic activity of MRC-5 cells was completely inhibited after 48 hours exposure in culture medium containing PMEDAP (10 micrograms/ml), or PMEA (25 micrograms/ml), respectively. Significant concentration dependent inhibition of cell proliferation caused by PMEDAP and/or PMEA was also observed in murine splenocytes. The analogs specifically inhibit proliferation of mitogen-activated T-lymphocytes. Modulation of subpopulations of peripheral blood cells under in vivo conditions was found in inbred SD animals. Intraperitoneal administration of PMEDAP to young healthy SD animals induced the decrease of the CD4+/CD8+ value from 1.3-1.6 to 0.72 while i.p. application of PMEA caused a decrease of the same ratio to 0.62.
Keywords: Adenine; kultivované buňky; Rats; Lymphoma, T-Cell; potkani Sprague-Dawley; buněčné dělení; injekce intraperitoneální; CD4-CD8 Ratio; adenin; antivirové látky; Cell Division; Mice; Antineoplastic Agents; poměr CD4 a CD8 lymfocytů; krysa rodu Rattus; slezina; Cells, Cultured; Injections, Intraperitoneal; protinádorové látky; zvířata; plíce; Humans; myši; lymfom T-buněčný; Rats, Sprague-Dawley; Antiviral Agents; Spleen; Lung; lidé; Animals